The role of the surgical robot in gender-affirming surgery: a scoping review - Karen M. Doersch; Lily Kong; Christodoulos Kaoutzanis; Ty Higuchi (Therapeutic Advances in Urology)
Background: Gender-affirming surgery is a growing field to address gender dysphoria, which is an increasingly recognized condition. The surgical robot is an excellent tool for performing some gender-affirming procedures and has been utilized extensively in both feminizing and masculinizing surgery. Objectives: To provide an overview for the use of the surgical robot in gender-affirming surgeries. Design: This is a scoping review. Methods: A literature search was conducted by the authors via PubMed and Google Scholar. Results: The ability of the robot to operate within the pelvis makes it an excellent platform for performing colpectomy with colpocleisis, hysterectomy, and vaginoplasty. A variety of grafts and flaps are amenable to robotic employment in the setting of gender-affirming surgeries. Finally, many revisions can be performed via the robotic approach, regardless of the approach of a patient’s primary surgery. Conclusion: The surgical robot is a useful tool for performing gender-affirming surgeries, including primary surgeries and revisions. Future research will continue to define roles for the robot in the setting of gender-affirming surgery, improve outcomes, and develop novel techniques.